Microalgae cultivation in offshore floating photobioreactor: State-of-the-art, opportunities and challenges - Khor, W.H. (Elsevier B.V., 2022)
The wide application of microalgae in health foods, nutritional feeds, aquaculture, pharmaceutical extracts, and biofuel production, has brought about the advancement of the microalgae cultivation industry. However, commercial-scale cultivation of microalgae still faces one major challenge, which is its economic feasibility, with lower cost and energy consumption. Developing floating photobioreactors to be utilized in offshore open water areas has gained more interest recently as it can diminish the cost effects of onshore land utilization, while seeking for additional benefits, such as regulated temperature, proximity to sunlight and nutrient supplies, and integrated ocean renewable energy. Thereby, this is timely to explore the potential of floating photobioreactors for microalgae cultivation in the offshore region. This review deliberately presents the characteristics of offshore environments and their potential effects on microalgae cultivation, as factors such as location selection, heat capacity, and utilization of cultivation resources are significantly different from conventional land-based cultivation. Compared to land-based photobioreactors, the design of floating photobioreactors has the opportunity to adopt hydrodynamical design; by utilizing the external force from ocean waves to generate internal liquid sloshing for improving the mixing of cultivation medium. While offshore-based microalgae cultivation is considerably new as part of blue economy and mariculture, this review provides insights into the opportunities for further advancement of offshore microalgae cultivation technologies. The encouraging factors for hybridization of offshore microalgae cultivation include mariculture, carbon dioxide capture and utilization, hydrogen production, and ocean thermal energy. Such understandings are vital to improving microalgae cultivation in offshore floating photobioreactors towards a valuable alternative to the current concerns in developing commercial scale of the microalgae industry. Various challenges in biological issues, economic and environmental challenges, installation and maintenance, as well as destructive hydrodynamic loads are also discussed. Â© 2022 Elsevier B.V.